A comparison of potential psychiatric drug interactions from six drug interaction database programs. (May 2019) - Monteith, Scott; Glenn, Tasha
Highlights: Compared category of potential DDI from 6 drug interaction database programs. Searched 100 drug interaction pairs containing psychiatric drugs. Overall percent agreement was 66%; overall Fleiss kappa interrater reliability was fair. Potential DDI categories from drug interaction database programs often differ. When assistance is needed, check more than one drug interaction database program. Abstract: Harmful drug-drug interactions (DDI) frequently include psychiatric drugs. Drug interaction database programs are viewed as a primary tool to alert physicians of potential DDI, but may provide different results as there is no standard to define DDI. This study compared the category of potential DDI provided by 6 commercial drug interaction database programs (3 subscription, 3 open access) for 100 drug interaction pairs. The pairs involved 94 different drugs; 67 included a psychiatric and non-psychiatric drug, and 33 included two psychiatric drugs. The category assigned to the potential DDI by the 6 programs was compared using percent agreement and Fleiss' kappa interrater reliability measure. The overall percent agreement for the category of potential DDI for the 100 drug interaction pairs was 66%. The Fleiss kappa overall interrater agreement was fair. The kappa agreement was substantial for interaction pairs with any severe category rating, and fair for interaction pairs with any major category rating. The category of potential DDI for drug interaction pairs including psychiatric drugs often differs among drug interaction database programs. Modern technology allows easy access to several interaction database programs. When assistance from a drug interaction database program is needed, the physician should check more than one program.